The relationship of chronic malnutrition to adolescent girls’ cognition in Indonesia: A systematic review. - Musfira; Hadju, Veni (Nutrición Clínica y Dietética Hospitalaria, 2025)
Background: Chronic malnutrition, including chronic energy deficiency, stunting, and anemia, significantly impacts cognitive development in adolescent girls in Indonesia. Objective: A systematic review was conducted to examine the relationship between chronic undernutrition and cognitive function. Method: In this systematic use the PRISMA framework. Studies from the past 10 years, including cross-sectional or cohort observational quantitative designs, were analyzed using Loney’s critical appraisal tool. From an initial 781 articles, 13 met the inclusion criteria. Result: Findings revealed anemia as a key factor affecting cognitive function and learning, with reduced hemoglobin levels linked to poor concentration, problem-solving, and academic performance (p<0.05). Anemic adolescents were 3 to 37 times more likely to exhibit poor learning outcomes (75%-92.5% low performance). Stunted adolescents had lower MMSE scores (median = 24, p = 0.013) and IQ (<84) compared to their non-stunted peers. The combination of anemia and stunting may exacerbate cognitive deficits, though research on this interaction is limited. Conclusion: Anemia was identified as having the most pronounced impact on cognitive function, highlighting the need for targeted interventions to prevent and manage anemia, improve academic performance, and enhance the quality of life of adolescent girls. Further research is recommended to establish causal relationships and inform effective policy strategies.